2001
DOI: 10.1063/1.1367259
|View full text |Cite|
|
Sign up to set email alerts
|

Non-Lorentzian zero-phonon holes and new insights on nonphotochemical hole burning: Al-phthalocyanine in hyperquenched glassy water

Abstract: Articles you may be interested inA model for persistent hole burned spectra and hole growth kinetics that includes photoproduct absorption: Application to free base phthalocyanine in hyperquenched glassy ortho-dichlorobenzene at 5 K Electronic dephasing and electron-phonon coupling of aluminum phthalocyanine tetrasulphonate in hyperquenched and annealed glassy films of ethanol and methanol over a broad temperature range Zero-phonon hole ͑ZPH͒ profiles and hole spectra that span about eight decades of burn flue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(67 citation statements)
references
References 29 publications
5
61
1
Order By: Relevance
“…As evident from the data presented in Table 1, the parameters of the tunneling distribution observed for photosynthetic protein complexes are significantly different from those reported for hyperquenched glassy water and simple organic glasses [34][35][36][37] . The LH2 antenna complex, which was explored in detail earlier 38 and that contains bacteriochlorophyll a, not chlorophyll a, exhibited parameters in the same range…”
Section: Discussioncontrasting
confidence: 38%
See 3 more Smart Citations
“…As evident from the data presented in Table 1, the parameters of the tunneling distribution observed for photosynthetic protein complexes are significantly different from those reported for hyperquenched glassy water and simple organic glasses [34][35][36][37] . The LH2 antenna complex, which was explored in detail earlier 38 and that contains bacteriochlorophyll a, not chlorophyll a, exhibited parameters in the same range…”
Section: Discussioncontrasting
confidence: 38%
“…Roughly, the hole burning yield is sixty to several hundred times lower in protein complexes than in hyperquenched water and organic glasses [34][35][36][37] . This is reasonable, taking into account that the entities experiencing light-induced fluctuations (tunneling) are expected to be larger and heavier in protein than in the case of amorphous host comprised of small molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…where ⍀ exp(Ϫ2 ) represents the phonon-assisted tunneling rate; ⍀ is set to 7.6 ϫ 10 12 s Ϫ1 (10); and , the fluorescence lifetime, was determined to be 1.8 ns at 77 K. The parameters and ␣ each cause a distribution of hole-burning rates that leads to dispersive kinetics, and it has been shown that the distribution is by far the dominant factor for the first 80% of the total burn (8). values for the o parameter allow conclusions to be drawn regarding the relative order of the environment experienced by the chromophore, which in the present case consists of MF680 in the lipid-based mitochondrial membranes.…”
Section: Resultsmentioning
confidence: 99%